Editorial, Volume 5, Issue 1 - Kristy L Archuleta (Journal of Financial Therapy, 2014)
Welcome to Volume 5, Issue 1 of the Journal of Financial Therapy! In this issue, four scholarly papers are presented along with two profiles and a book review. These four papers address very important issues, such as mental health therapists’ competency in working with financial issues, financial stress of college students, parental messages about money, and financial advice media.
Keywords: financial therapy; Financial Therapy Association; Journal of Financial Therapy